2018
DOI: 10.1002/uog.17435
|View full text |Cite
|
Sign up to set email alerts
|

Morphological ultrasound types known as ‘blob’ and ‘bagel’ signs should be reclassified from suggesting probable to indicating definite tubal ectopic pregnancy

Abstract: Blob and bagel signs seem to be the most common presentations of a tubal EP on TVS. Although they cannot be considered as a definitive sign of EP, their PPV is very high (> 95%); such women should therefore be considered at very high risk for having a tubal EP and should be treated as such. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Some researchers believe that, in many cases, ultrasound findings are non‐specific and they propose that a conclusive diagnosis of tubal EP can be made only in cases in which a gestational sac containing an embryo or a yolk sac is visible, whilst the other morphological types should be classified as probable EP. This approach has been questioned by others, who showed that conclusive ultrasound diagnosis of tubal EP could be made in most cases regardless of the morphological type.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers believe that, in many cases, ultrasound findings are non‐specific and they propose that a conclusive diagnosis of tubal EP can be made only in cases in which a gestational sac containing an embryo or a yolk sac is visible, whilst the other morphological types should be classified as probable EP. This approach has been questioned by others, who showed that conclusive ultrasound diagnosis of tubal EP could be made in most cases regardless of the morphological type.…”
Section: Introductionmentioning
confidence: 99%
“…The retrospective and single‐centre nature limit our ability to suggest that M4 be introduced throughout Australia. A prospective multicentre interventional study could be undertaken, but it would require clear definitions of a PUL1, with clarity around what constitutes a definitive EP on TVS 16 . Considering that many early pregnancy units are staffed by registrars/residents and clinical fellows, proficiency in sonographic EP diagnosis must also be ensured in study design.…”
Section: Discussionmentioning
confidence: 99%
“…This is a retrospective observational diagnostic accuracy study, Women diagnosed with PUL were managed according to EPASspecific protocol that relies on an hCG ratio (48-h hCG/0-h) 16 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Definitive diagnosis of ectopic pregnancy can be achieved by TVS, but it relies on a precise analysis of ultrasound findings [1,15-19]. However, in most emergency units, the initial TVS is usually performed by trainees or sonographers with basic expertise in OB/GYN scanning.…”
Section: Discussionmentioning
confidence: 99%